english: english - Wahyuni, Kiki; Octavianita , Ayu; Nur, Suryadi Amdhan; Handayani, Tuti; Ihsan, Muhammad Taufik (Jurnal Riset dan Inovasi Pembelajaran, 2021)
The goal of this study is to find out how instructors employ the Communicative Language Teaching approach in the English classroom, as well as the strategies and resources they use to help students develop their speaking skills.This can be seen from the class activities, speaking materials until the strategies that has been implemented in some research. This article takes the form of a review of documents and literatures, with an evaluation of knowledge as the basis. As a result, as a teacher, you may learn from other countries that have successfully implemented and developed CLT in improving students' speaking skills.